MATERNITY AND POETIC LANGUAGE: AN APPROACH TO THE POETRY OF BLANCA VARELA - Luján Sandoval, Sergio (2019)
The present work revolves around the approach of Blanca Varela's poetry regarding the amalgamation that results between motherhood and poetic language. For that purpose, we make use of a theoretical device based on the proposals of Lakoff and Johnson on the types of metaphors, as well as the notion of "metapoetry", understanding it as a thematic aspect of poetry that becomes self-reflexive and self-referential. Taking this into account, we intent to unravel and argue that there is a matrix project, like a backdrop, between the maternal phenomenon (mother-child relationship) and the linguistic phenomenon (poet- poem relationship).